Effect of Caponization on Meat Quality and Proximate Composition of Slow-Grow ing Indbro Brown Layer Cockerels - T, Srilatha; Devatkal, Suresh K; Kishore, Karnati; Kotaiah, Talapaneni; Supriya, Ratna; Yadagiri, Chandana (Journal of Meat Science, 2026)
The intensive breeding of laying hens for egg production has led to excess  production of cockerels, which are not economical for broiler production. This  issue may be addressed by subjecting the cockerels to castration, fattening, and  marketing them as specialty chicken meat targeting a niche market. Hence,  in this study, meat quality characteristics of caponized dual-type poultry  variety (Indbro) were compared with non-caponized and commercial broiler  meat. Dressing percentage and breast yield were significantly (p
Keywords: Indbro Cockerel; Caponization; meat quality; Fatty acid profile; commercial white broilers